2015
DOI: 10.1039/c4nr05982d
|View full text |Cite
|
Sign up to set email alerts
|

Complementary analysis of the hard and soft protein corona: sample preparation critically effects corona composition

Abstract: Here we demonstrate how a complementary analysis of nanocapsule-protein interactions with and without application media allows gaining insights into the so called hard and soft protein corona. We have investigated how both human plasma and individual proteins (human serum albumin (HSA), apolipoprotein A-I (ApoA-I)) adsorb and interact with hydroxyethyl starch (HES) nanocapsules possessing different functionalities. To analyse the hard protein corona we used sodium dodecyl sulphate polyacrylamide gel electropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
164
2
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(186 citation statements)
references
References 47 publications
5
164
2
7
Order By: Relevance
“…31 In addition, it is known that the protein adsorption pattern is highly influenced by surface functionalization of nanoparticles. 24,32,33 We found that the absolute number of bound proteins per defined surface of nanoparticles is significantly higher (Fig. 3C) for negatively charged nanoparticles (PS-COOH) in comparison to un-functionalized (PS), or positively charged nanoparticles (PS-NH 2 ).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…31 In addition, it is known that the protein adsorption pattern is highly influenced by surface functionalization of nanoparticles. 24,32,33 We found that the absolute number of bound proteins per defined surface of nanoparticles is significantly higher (Fig. 3C) for negatively charged nanoparticles (PS-COOH) in comparison to un-functionalized (PS), or positively charged nanoparticles (PS-NH 2 ).…”
Section: Resultsmentioning
confidence: 88%
“…Interestingly, the soft protein corona is not shown by TEM to be as uniformly distributed and wellrounded, but rather as an undefined network surrounding the nanoparticle. Generally 2,20 it is described as highly dynamic layer of proteins which have high exchange rates and low binding affinities towards the nanoparticle. By adding trehalose and uranyl acetate (UA) for TEM sample preparation, the highly dynamic structure is fixed.…”
Section: Resultsmentioning
confidence: 99%
“…For example, human serum albumin (HSA) adsorbed on hydroxyethyl starch nanocapsules could be detected by ITC, while there was no trace of HSA when evaluated by SDS-PAGE. 32 Hence, it is pivotal to choose suitable analytical techniques to accurately characterize protein corona properties since protein corona is related with physicochemical properties and biological identity of NPs.…”
Section: Instrumental Analysis For Evaluating Protein Coronamentioning
confidence: 99%
“…The hard corona is a single layer of proteins directly bound to the NP surface with high affinity, forming a stable coating. The soft corona, which covers the hard corona, is loosely associated and, therefore, promotes dissociation and rapid biomolecule exchange (Winzen et al 2015). Previous studies have demonstrated that the protein corona directly impacts the nano-cellular interface, thereby determining NP deposition efficiency, membrane interactions, degree of endocytosis, and biocompatibility (Chanana et al 2013;Lesniak et al 2013;Treuel et al 2014).…”
Section: Introductionmentioning
confidence: 99%